Pengaruh Intervensi Reflex Integration Program pada Individu dengan Autism Spectrum Disorder : Sebuah Literature Review - Fatma Nofriza; Dini Hanifa Putri (Universitas Negeri Medan, 2025)
Autism Spectrum Disorder (ASD) is a pervasive developmental disorder characterized by difficulties in social communication and interaction, and it is frequently associated with the persistence of Retained Primitive Reflexes (RPR). Unintegrated RPR can serve as an early marker for ASD, driving the necessity for effective interventions. This study aimed to determine the impact of implementing the Reflex Integration Program (RIP) on children and adolescents with ASD. The methodology employed was a Systematic Literature Review (SLR), analyzing eight relevant journals, where most studies utilized a pre-test and post-test experimental design and focused on the Masgutova Neurosensorimotor Reflex Integration (MNRI) intervention. The research findings indicate that RIP exerts a significant positive influence on various developmental aspects of children with ASD, encompassing improvements in social interaction, communication, emotional regulation, motor skills, sleep quality, and behavioral flexibility, alongside reductions in hyperactivity and aggression. It is concluded that RIP holds potential as a valuable therapeutic option for enhancing the development of children with ASD, particularly in addressing socio-communicative deficits, and can be effectively combined with other interventions.